Workshop on Enhancing Diagnostic Accuracy: Strategies to Mitigate Lipemic Interference in Urea and Creatinine Testing Using Alpha-Cyclodextrin - Siti Ramadhani; Riri Safitri; Nur Afni Heryanti Octavia (JURNAL PENGMAS KESTRA (JPK), 2026)
The quality of blood samples dictates the validity of clinical laboratory testing. Lipemic serum conditions frequently cause analytical issues due to high lipid particles that interfere with photometer readings in chemistry analyzers. This community service (PkM) program, formatted as a workshop, was implemented to broaden the knowledge and technical proficiency of laboratory personnel. The event involved 30 students from the Medical Laboratory Technology program as participants. The implementation included interactive lectures, visual demonstrations, in-depth discussions on clinical chemistry principles, and hands-on sample management practices in the laboratory. Educational and training materials were specifically designed to ensure that participants could effectively resolve lipid interference and understand the function of alpha-cyclodextrin as a safe clearing agent that does not alter analyte concentrations. The results demonstrated tangible progress among participants in detecting analytical interference caused by lipemia, evidenced by a 33.5-point average increase in cognitive knowledge scores and a 95.0% participant satisfaction rate. Participants are now capable of executing correct pre-analytical steps using alpha-cyclodextrin and obtaining more accurate urea and creatinine measurements. This program underlines the importance of integrating technical problem-solving into human resource competency enhancement activities in the laboratory. Improving participants' understanding of managing problematic specimens contributes directly to enhancing the quality of clinical chemistry examination results and supports the creation of professional, precise, and reliable healthcare services for the community..